The impact of the shadow economy on taxation in Cambodia - Mong, Mara; Lim, Siphat (Edelweiss Applied Science and Technology, 2024)
A multiple regression analysis was conducted to assess the influence of the shadow economy, inflation rate, and GDP growth rate on tax revenue. The regression model utilized level data, and the two-step Engle and Granger cointegration test confirmed the absence of spurious relationships between the dependent and independent variables. Various diagnostic tests associated with OLS methods were performed, including assessments for multicollinearity, heteroscedasticity, and serial autocorrelation. To ensure the robustness of the standard errors, the HAC standard errors and covariance were applied. The empirical findings of this research demonstrated that the growth of the shadow economy has a statistically significant negative impact on tax revenue in Cambodia. Furthermore, the results indicated a negative relationship between inflation and tax revenue, while a positive correlation was found between real GDP growth and tax revenue.